Intersection of Community Violence and Prenatal Substance Exposure: A Spatiotemporal Analysis - Haricharan, Ramanathapura; Thompson, Stephanie; Annie, Frank; Maduakonam, Chisom (American Journal of Perinatology, 2024)
Maternal substance use during pregnancy is a known risk factor for poor birth outcomes and lifelong health consequences. In addition, exposure to domestic and community violence can be associated with adverse birth outcomes. Due to limited research examining public health challenges linked to prenatal substance exposure (PSE)/neonatal abstinence syndrome (NAS) at the population level, we examined possible geographic and temporal intersections between (1) community violence and PSE/NAS, and (2) community gun violence and PSE/NAS.We conducted a study using abstracted records of neonates born at a tertiary referral hospital from 2012 to 2019 having a diagnosis code for PSE/NAS (n = 1,523). Cases of community violence were identified using a hospital-based Trauma Registry during the 2012 to 2019 period (n = 1,580). We identified zones of spatial clustering and geographic overlap between community violence and PSE/NAS using emerging hot spot analysis.Geographic and temporal clustering of PSE/NAS occurred. PSE/NAS had statistically significant zones of overlap with community assault cases (New Hot Spot 15 zones, Consecutive 5 zones, Sporadic Hot Spot 62 zones with a p < 0.01). PSE/NAS also clustered with community gun violence (New Hot Spot 11 zones, Consecutive Hot Spot 90 zones, Intensifying Hot Spot 13 zones, Sporadic Hot Spot 20 zones with a p < 0.01).Spatiotemporal overlap occurred between community violence and the adverse neonatal event of PSE/NAS. By allocating resources to identified geographic areas of increased risk, the health of vulnerable communities can be improved.
Keywords: community violence; neonatal abstinence syndrome; prenatal substance exposure